Is the comorbidity of a mild traumatic brain injury a factor influencing the reduction of symptoms of post-traumatic stress disorder in veterans - Smashna, Olena (Medicinski časopis, 2024)
Objective. Investigation of the relationship between the severity of clinical symptoms and functioning and cumulative severity of TBI in veterans with PTSD and mTBI after an 8-week comprehensive intervention (combining a psychotherapy with transcranial direct current stimulation (tDCS). Methods. 329 veterans (PTSD (n = 109), mTBI (n = 112), PTSD + mTBI (n = 108) were examined using The Four-Dimensional Symptom Questionnaire — 4DSQ, WHODAS 2.0 and BAT-L. Standardized treatment was provided as well as psychotherapeutic intervention - a combination of psychoeducation with motivational interviewing and acceptance and commitment therapy for PTSD (ACT) and transcranial direct current stimulation (tDCS). Results. Depressive symptoms in PTSD combine with impaired social activity, impaired functioning due to the disease, self-care defects. n the PTSD/TBI group, psychological distress was associated with the depth of cognitive impairments, in contrast to the PTSD group, where no such pattern was found. Also, in contrast to the PTSD group, there was a noticeable increase in daytime activity with a reduction in depressive symptoms. Сonclusion The presence of excitement and hyperactivation in TBI patients with pronounced consequences of combat traumatic brain injury, even in the absence of clinically defined PTSD, as well as the relationship between the expressiveness of TBI, not related to combat trauma, and the level of depressive symptoms indicate the need for routine examination of all patients with TBI for the presence of comorbid PTSD and depression.